Identification and characterization of dystrophin-locus-derived testis-specific protein: A testis-specific gene within the intronic region of the rat dystrophin gene - Keitaro YAMANOUCHI; Shizuka KATO; Yukie TANAKA; Masanari IKEDA; Yukina OSHIMO; Takanori SHIGA; Kei HATAMOTO; James CHAMBERS; Takuya IMAMURA; Ryuji HIRAMATSU; Kazuyuki UCHIDA; Fuko MATSUDA; et al. (The Society for Reproduction and Development, 2024)
The mammalian X chromosome exhibits enrichment in genes associated with germ cell development. Previously, we generated a rat model of Becker muscular dystrophy (BMD) characterized by an in-frame mutation in the dystrophin gene, situated on the X chromosome and responsible for encoding a protein crucial for muscle integrity. Male BMD rats are infertile owing to the absence of normal spermatids in the epididymis. Within the seminiferous tubules of BMD rats, elongated spermatids displayed abnormal morphology. To elucidate the cause of infertility, we identified a putative gene containing an open reading frame situated in the intronic region between exons 6 and 7 of the dystrophin gene, specifically deleted in male BMD rats. This identified gene, along with its encoded protein, exhibited specific detection within the testes, exclusively localized in round to elongated spermatids during spermiogenesis. Consequently, we designated the encoded protein as dystrophin-locus-derived testis-specific protein (DTSP). Given the absence of DTSP in the testes of BMD rats, we hypothesized that the loss of DTSP contributes to the infertility observed in male BMD rats.